Analisis Rasio Keuangan Perusahaan Food and Beverage yang Tercatat di Bursa Efek Indonesia Periode 2019-2023 - Narulita, Friska Dhea; Soraya, Bunga; Baderi, Rahmawati Nur; Hidayati, Cholis (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this research is to evaluate the financial performance of the food industry, namely PT Nippon Indosari Corpindo Tbk, PT Mayora Indah Tbk, and PT Indofood CBP Sukses Makmur Tbk using financial ratio evaluation from 2019 to 2023. The method applied is a descriptive quantitative approach by reviewing the company's financial statements within that period. The indicators analyzed are liquidity ratios, activity ratios, solvency ratios, and profitability ratios. The results of the study revealed that CBP has the best performance in terms of liquidity, while for the activity ratio, the company shows optimal effectiveness in managing receivables. In terms of solvency, Nippon Indosari Tbk recorded a lower debt-to-asset ratio than other companies. Meanwhile, in terms of profitability, CBP recorded the highest net profit margin, showing significant efficiency in managing operating costs.